NEAR MISS: CLINICAL CASES OF PREGNANCY OUTCOMES IN WOMEN WITH COVID-19 - Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Сергей Валерьевич Рыбников; Кира Борисовна Мозес; Ольга Борисовна Карелина; Елена Владимировна Золото (The Publishing House Medicine and Enlightenment, 2022)
COVID-19 leads to cytokine storm, systemic inflammatory response and coagulopathy, which is one of the worst prognostic factors. Coagulopathy in COVID-19 is accompanied by a pronounced increase in the level of D-dimer and degradation products of fibrin / fibrinogen, while deviations of other indicators (prothrombin time, activated partial thromboplastin time, platelet count) are relatively rare at the onset of the disease. All pregnant women are offered a screening test for coagulation, including the determination of the level of D-dimer and fibrinogen. For coagulopathy associated with COVID-19, empiric anticoagulant therapy is required to prevent venous thrombosis and thromboembolism, as well as standard maintenance therapy for sepsis-induced coagulopathy or disseminated intravascular coagulation syndrome.